2005
DOI: 10.1379/csc-156.1
|View full text |Cite
|
Sign up to set email alerts
|

Association of hsp70-2 and hsp-hom gene polymorphisms with risk of acute high-altitude illness in a Chinese population

Abstract: High-altitude illness (HAI) is a potentially fatal condition involving genetic and environmental components. Accumulated experimental evidence suggests that heat shock proteins (Hsps), especially HSP70, can protect cells and organs against different types of damage. We investigated whether genetic variation in constitutive and inducible hsp70 genes could be associated with risk of HAI. The association between polymorphisms of the HSP70 family genes and risk of HAI was determined in 56 patients with HAI and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 56 publications
1
25
1
1
Order By: Relevance
“…In ankylosing spondylitis, differences in hsp70-1 and hsp70-2 genotypes among ankylosing spondylitis patients and controls appear to be due to the linkage disequilibrium between HSP70 alleles and HLA-B*27 (Fraile et al 1998). We also found that individuals with hsp70-2 ϩ1267B/B, hsp70-hom ϩ2437A/B, ϩ2437B/B genotypes are more susceptible to high-altitude illness, whereas those with hsp70-hom ϩ2437A/B genotype are tolerant to low oxygen (Zhou et al 2005).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In ankylosing spondylitis, differences in hsp70-1 and hsp70-2 genotypes among ankylosing spondylitis patients and controls appear to be due to the linkage disequilibrium between HSP70 alleles and HLA-B*27 (Fraile et al 1998). We also found that individuals with hsp70-2 ϩ1267B/B, hsp70-hom ϩ2437A/B, ϩ2437B/B genotypes are more susceptible to high-altitude illness, whereas those with hsp70-hom ϩ2437A/B genotype are tolerant to low oxygen (Zhou et al 2005).…”
Section: Discussionmentioning
confidence: 48%
“…These genes are polymorphic, potentially accounting for variation in their functions and susceptibility to stress tolerance (Favatier et al 1997;Wu et al 2004). Some studies reported possible associations of single nucleotide polymorphisms (SNPs) in the hsp70 genes with Parkinson's disease (Wu et al 2004), abacavir hypersensitivity (Martin et al 2004), autoimmune diseases (Pugliese et al 1992;Favatier et al 1997;Fraile et al 1998;Vargas-Alarcon et al 2002), lung cancer (Rusin et al 2004), and acute high altitude illness (Zhou et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Hsp70 protein and its antibody have been identified as being involved in the pathogenesis of hypertension, atherosclerosis, coronary heart disease, acute heat-induced illness and heat stroke (Gromadzka et al, 2001;Wu et al, 2001;Pockley et al, 2003;Jin et al, 2004). Hsp70.1 and Hsp70.2 are polymorphic, potentially accounting for variation in their functions and susceptibility to stress tolerance (Ross et al, 2003;Wu et al, 2004;Zhou et al, 2005). Single nucleotide polymorphisms (SNPs) in the coding region of Hsp70 genes could affect peptide-binding kinetics or affinity of the Hsp70 proteins and ATPase activity, while nucleotide changes in the flanking regions (promoter and 5 0 , 3 0 -untranslated region (UTR)) might affect inducibility, degree of expression or stability of Hsp70 mRNA.…”
Section: Hsp70 Genotype and Heat Stressmentioning
confidence: 99%
“…The gene is polymorphic, potentially accounting for variation in its functions and susceptibility to stress tolerance (Zhou et al 2005). An adenine (A) to guanine (G) polymorphism at HspA1B +1267 has been described; however, the polymorphism does not lead to any amino acid change in the Hsp70 protein.…”
Section: Introductionmentioning
confidence: 99%